Prostate cancer treatment in Portugal: a nationwide analysis - Botelho, F (2023)
Different treatment options exist for localized prostate cancer. Treatments performed in high-volume hospitals are associated with better results. Our objective was to describe time trends in prostate cancer treatments in Portugal and case volume per hospital. We used the national database of diagnosis-related group of the Portuguese Central Administration of the Health System to describe the number of radical prostatectomy (RP), brachytherapy (BT) and external radiotherapy (eRT) treatments performed in all National Health System hospitals. There was a rapid increase in the annual number of RP until 2006 and then a deceleration; BT treatments augmented significantly until 2011. The utilization of eRT also increased, surpassing RP after 2010. From the 46 hospitals performing RP, only eight had a case-volume > 50 treatments/year, and from the nine hospitals performing BT, only four accomplished > 15 treatments/year. In the 11 hospitals with eRT, nine performed > 50/year. Regarding RP, there was negative correlation between the hospital volume and length of stay (r = − 0.303; p = 0.041). In the Portuguese National Health Service there was a steep increase in the number of prostate cancer treatments, and there is an ample margin for concentration of RP and BT treatments, for improvement of the hospitals case volume. © 2023, The Author(s).